Koalisi Partai Nasionalis dan Partai Islam Pilkada Labuhan Batu Tahun 2020 Ditinjau Menurut Fiqh Siyasah - Nurhaliza, Siti (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study examines the Implementation of the Nationalist Party and Islamic Party Coalition in the 2020 Labuhanbatu Regency Election, then the considerations made by the Nationalist Party and Islamic Party to Choose a Coalition in the Labuhanbatu Regency Election 2020. This research is a field study research with a qualitative approach, Data sources The primary ones are: the Prosperous Justice Party, the Indonesian Democratic Party of Struggle, the Hanura Party, the National Awakening Party and the KPU in the election of regional head candidates in Labuhanbatu Regency in 2020 and also the winning team for the pair H. Erik Atrada and Ellya Rosa. Secondary data sources are books and documents, observation data collection techniques, interviews and documentation, data analysis techniques using qualitative descriptive. The results of this study indicate that the formation of the coalition that was built between the Nationalist Party and the Islamic Party was not based on ideological similarities but, vision, mission and background as a candidate for Regent which became the basis for forming a coalition. In addition, the support of 20% from a combination of political parties is also one of the reasons for the formation of a coalition which is a requirement for candidacy through the Coalition route. The form of this coalition is a coalition that meets the KPU's requirements with the support of 20% of the DPRD seats.